EXAMINATION OF CRITICAL THINKINGS OF INDIVIDUAL AND TEAM SPORTS PARTICIPANT UNIVERSITY STUDENTS IN TERMS OF SOME DEMOGRAPHIC VARIABLES - Nahit Özdayı (ümit doğan üstün, 2019)
The aim of this study was to examine the critical thinking tendencies of university students who are interested in individual and team sport in terms of demographic variables. The study was conducted with 200 students, 116 males (58.0%) and 84 females (42.0%). In the study to collect data Turkish version of California critical thinking tendency scale was used. The distribution of the collected data was investigated and normal distribution was determined. For this reason, statistical analysis was performed with parametric test methods. According to the results of the study, there was no statistically significant difference on the variable critical thinking tendency according to gender, age, sports branch, commitment to the team, active sport participation and the mother education status (p>0.05). However, there was a statistically significant difference according to father education status (F 2, 981 p=0.033<0.05). As a result, it can be said that gender, age, sports branch, commitment to the team, active sport participation and mother education status do not make any significant difference on the variable critical thinking tendency. However, because of there was a significant difference according to the educational level of the father, it was thought that father education status is one of the determinants of the students' critical thinking tendencies engaging in individual or team sports.